Dissemination of Appropriate Technology Importance and Legal Basis of BUMDES in the Pandemic Era - Yordan Gunawan; Muhamat Ridho Yuliyanto (International Journal of Research in Community Services, 2022)
This action took place in Potorono Village. The biggest issue that the residents of Potorono face are the large population, although there are still many people who do not work. Essentially, the potential for employment prospects in Potorono Village for the local community is rather considerable, but it is not appealing enough to work for the local people. Meanwhile, the Covid 19 pandemic, which began in March 2020, has caused many village community companies to halt and fail to flourish correctly. Furthermore, Potorono Village residents' knowledge of the value of Village Owned Enterprises (BUMDES) has not been optimal for the development of village residents' companies. Furthermore, the village community has not properly harnessed the natural potential and its supporting job sectors to boost welfare. This service's efforts are in the form of dissemination and support with the proper technology, as well as comprehending BUMDES's duty as a legal body. Furthermore, the utilization of waste processing into finished commodities that can be sold is communicated to the community in order to strengthen the village economy. The Potorono community's approach technique is built on active and interactive involvement, as well as dissemination and support with the deployment of relevant technologies to the community. As a result of this service, the community will understand the benefits of having BUMDES as a legal body in their area, as well as how to use technology to assist rural communities in growing their local economies.